The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.2169/internalmedicine.43.306
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hemiagenesis with Postpartum Silent Thyroiditis

Abstract: A 28-year-old woman with thyroid hemiagenesis, who had been diagnosed as having Graves' disease, became pregnant during the course of methimazole treatment. The treatment was terminated in the second trimester. She delivered a normal infant at full term. She became thyrotoxic 3 months after the delivery, hypothyroid 6 months after the delivery, and finally euthyroid 11 months after the delivery without undergoing any treatment. This clinical course indicates that she developed silent thyroiditis after the deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Most observed cases of thyroid hemiagenesis have been found only incidentally after patients have been examined for thyroid conditions since the absence of one thyroid lobe usually does not cause clinical symptoms by itself [2][3][4][5][6][7][8][9]. There has been only one survey to establish its prevalence among patients with thyroid disorders [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most observed cases of thyroid hemiagenesis have been found only incidentally after patients have been examined for thyroid conditions since the absence of one thyroid lobe usually does not cause clinical symptoms by itself [2][3][4][5][6][7][8][9]. There has been only one survey to establish its prevalence among patients with thyroid disorders [2].…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one survey to establish its prevalence among patients with thyroid disorders [2]. Since thyroid hemiagenesis is very rare entity, many case reports have been published describing the association with other thyroid diseases or congenital defects, mostly cardiac [2][3][4][5][6][7][8][9]. The associated diseases in the intact thyroid lobe include benign adenoma, multinodular goiter, hyperthyroidism, chronic thyroiditis, Graves' disease, and rarely carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly prior to becoming pregnant, an increase in thyroperoxidase autoantibodies (TPOAb) was observed in this woman. In another Japanese woman with thyroid hemiagenesis, GD was present in the pregnancy that preceded the postpartum period during which PPT appeared (45). Other case reports of PPT following GD have appeared in the literature (46, 47), one being noteworthy because of the sequence onset of GD → PPT → relapse of GD (47).…”
Section: Postpartum Thyroid Autoimmunitymentioning
confidence: 99%
“…However, the etiopathogenesis of this condition, its clinical significance, impact on thyroid function, and development of associated thyroid pathologies as well as the management of patients in whom the anomaly is diagnosed are still a matter of debate (1,(4)(5)(6)(7). To date, individual case studies have been reported most often, mainly as an anatomical curiosity or as a diagnostic dilemma, whereas the literature lacks methodological studies of large groups of patients presenting THA, which would provide objective answers to these controversies (4,5,(8)(9)(10)(11)(12)(13). Since hormone production by a single thyroid lobe is sufficient to maintain clinical euthyroidism, provided no concomitant thyroid pathology exists, THA has been up to now regarded as a rather benign developmental variant requiring no treatment.…”
Section: Introductionmentioning
confidence: 99%